PRACTICE NOTES SOFTWARE «VERTEBRAL FRACTURE ASSESSMENT» FOR DUAL-ENERGY BONE DENSITOMETER «DISCOVERY W» IN THE DIAGNOSIS OF OSTEOPOROSIS - E M Eidlina (Остеопороз и остеопатии, 2012)
The authors studied the feasibility of an additional software application for dual-energy X-ray bone densitometer series «Discovery W» (HOLOGIC inc., USA). 45 patients with osteoporotic vertebral compression fractures underwent technique of «Vertebral Fracture Assessment» in one session with standard densitometry at the lumbar spine and proximal femur. This program is based on a semi-quantitative morphometry of the spine (N.K. Genant; 1993) is an alternative to radiography for the diagnosis of vertebral fractures. Determination of the index values of the vertebral bodies by this method allows identification not only explicit, but subtle compression vertebral fractures of both thoracic and lumbar spine. The methodology should be ordered by an osteoporosis specialist, evaluated by radiologist, it can be performed in one session with standard densitometry procedure. Assessment of the bone structure of the vertebral bodies by this imaging technology is not feasible.